Feasibility of metabolomic analysis in assessing coral reefs environments. - Hedi Indra Januar; Boedi Hendrarto; Ekowati Chasanah (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2010)
This study aimed to explain the feasibility of fingerprint and chemical marker metabolomicanalysis in assessment of coral reefs environments. Based on literature review, both analysismight be implemented on coral reef environment assessment, with their specific strength andweakness. Fingerprint metabolomic is a comprehensive approach in assessing the condition ofcoral reefs bioindicator that is having environmental stresses. It require high technology chemicalinstrumentation and complicated statistical approach in post data analysis. On the other hand,chemical marker metabolomic is more simplified in data analysis and instrumentation, but notcomprehensively assess the metabolite changes of bioindicator that is having environmentalstresses. To apply as high throughput screening in coral reefs assessment, subjectively the chemicalmarker method would be more feasible. One of the potential chemical marker that used iscembranoids, a bioactive compound from soft corals.